Management of Changes in Automotive Life Cycle - Florin STINGA; Irina SEVERIN; Elena LASCU; Ioana Alina MITRACHE; Bogdan DUMITRU (Communications of International Proceedings, 2020)
This article summarizes the changes flow during the vehicle's life cycle phase and presents an analysis of the changes' implementation ratio. In the automotive industry, harsh competition, the need for optimization of costs and continuous improvement leads manufacturers to improve their products to remain competitive in the marketplace continually. Following the data collection through the 3-year analysis regarding the modifications on the series vehicles, the article presents the stages of implementing the modifications on the vehicles in the production phase and their distribution depending on the nature of these changes. The permanent evolution to continually modify vehicle's parts, even during the production phase, appears necessary. This research presents the main stages of implementing the changes in the series vehicles, the types of changes, the sources of these changes, and the people involved in process. The series changes require special attention considering the implementation costs significantly exceeding the project phase's costs. Essential factors, such as fast implementation time, analysis and rapid solution identification, costs of modifying equipment, and the entire implementation management, but also the resources involved in this process, should be monitored. Considering the importance of these changes on series vehicles, the article summaries the stages of implementation of these changes and details the main areas of intervention.
Keywords: Process Management; Continuous Improvement; Process-Based Guidance.